Determinants of Tuberculosis Incidence Among Children Under Five in Karanganyar, Central Java, Indonesia - Ninik Hartini; Bhisma Murti; Setyo Sri Rahardjo; Sumardiyono; Yulia Lanti Retno Dewi (Journal of Epidemiology and Public Health, 2026)
Background: Tuberculosis (TB) remains a major infectious disease and a leading cause of mortality worldwide, with 10.8 million cases and 1.25 million deaths reported in 2023. Indonesia is classified as a high-burden TB country, with 78,566 cases reported among children under five years of age. Young children are particularly vulnerable due to their immature immune systems. In Karanganyar Regency, Central Java, Indonesia, 137 cases of TB among under-five children were recorded in 2023. This study aimed to analyze the risk factors associated with TB incidence among children under five in Karanganyar Regency. Subjects and Method: This study employed an analytic observational design using a case-control approach. A total of 200 children under five were randomly selected, comprising 50 TB cases and 150 non-TB controls. Data were analyzed using simple logistic regression and path analysis to examine direct and indirect relationships among variables. Results: The incidence of TB among children under five increased with a history of contact with TB patients (b = 0.18; 95% CI = 0.10–0.26; p < 0.001) and living in homes with high humidity (b = 0.09; 95% CI = 0.01–0.17; p = 0.019). Conversely, TB incidence decreased with good lighting (b = -0.11; 95% CI = -0.19 to -0.03; p = 0.005), presence of bedroom windows (b = -0.41; 95% CI = -0.51 to -0.31; p < 0.001), living room windows (b = -0.31; 95% CI = -0.41 to -0.22; p < 0.001), and residence in highland areas (b = -0.13; 95% CI = -0.21 to -0.06; p < 0.001). Nutritional status was negatively affected by TB (b = -0.30; 95% CI = -0.43 to -0.15; p < 0.001) and positively influenced by family income (b = 0.17; 95% CI = 0.03–0.31; p = 0.016), with income exerting both direct and indirect effects through TB. The path analysis model demonstrated good fit (Chi-square p = 0.068; RMSEA = 0.052; CFI = 0.981; TLI = 0.960). Conclusion:  The risk of TB among children under five increases with exposure to adult TB cases and living in humid housing conditions. Conversely, TB incidence decreases in children residing in well-lit homes with bedroom and living room windows and in highland areas. Nutritional status is influenced by both TB and family income, with income affecting TB directly and indirectly.